PERANCANGAN USER INTERFACE DAN USER EXPERIENCE E LEARNING DENGAN METODE DESIGN THINKING STUDI KASUS SMAN 1 KARAWANG - Irfan Maulana (Jurnal Rekayasa Perangkat Lunak dan Hardware, 2026)
The era of digitalization of technology and the internet is currently growing rapidly which has an impact on every activity and community activity. The Covid-19 pandemic since March 2020 has changed the process of teaching and learning activities in class with distance learning. SMAN 1 Karawang is a senior high school that at that time used technology and the internet by utilizing platforms such as Google Classroom, Google Form, Google Drive and Google Meet in the process of teaching and learning activities. However, in using the Google platform there are still deficiencies that students and teachers feel, such as attendance, making materials, and collecting assignments that must be separated from various media. This study intends to analyze and design the user interface and user experience design of e-learning as a solution to the problems found in SMAN 1 Karawang schools. The method used in this study uses Design Thinking in each stage of the user interface design process and user experience e-learning, as well as in design testing using usability testing with two Single Ease Question (SEQ) and System Usability Scale (SUS) methods. The results of this study resulted in the design of the user interface and user experience prototype design of e-learning and in the usability testing with the Single Ease Question (SEQ) measurement, respondents got responses with two ratings, namely 6 (easy) and 7 (very easy). As well as in the measurement of System Usability Scale (SUS) it gets a score of 70.5, where the results of the interpretation of the system usability scale score get Acceptability Ranges with the High range, it is included in Acceptable and on the Grade Scale it gets the Grade C range and on the Adjective Ratings it gets Good (good).